2002
DOI: 10.1097/00000542-200206000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Relevant Concentrations of Propofol Have No Effect on Adenosine Triphosphate–sensitive Potassium Channels in Rat Ventricular Myocytes

Abstract: Propofol had no effect on the sarcolemmal K(ATP) channel activities in patch clamp configurations and the mitochondrial flavoprotein fluorescence induced by diazoxide at clinically relevant concentrations (< 2 microm), whereas it significantly inhibited both K(ATP) channel activities at very high, nonclinical concentrations (> 5.6 microg/ml; 31 microm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 0 publications
0
22
0
1
Order By: Relevance
“…Electrophysiological experiments have shown that isoflurane may activate K ATP channels at a moderately acidic intracellular pH of 6.8 [16] or facilitate the opening of channels via the activation of protein kinase C [17]. In contrast, our previous patch-clamp experiments indicated that high supraclinical concentrations of propofol directly inhibited the cardiac K ATP -channel activity [18,19]. Ketamine also inhibits recombinant cardiac K ATPchannel activity in a concentration-dependent manner [20].…”
Section: Cardiac K Atp Channel (Sarcolemmal Channel)mentioning
confidence: 76%
“…Electrophysiological experiments have shown that isoflurane may activate K ATP channels at a moderately acidic intracellular pH of 6.8 [16] or facilitate the opening of channels via the activation of protein kinase C [17]. In contrast, our previous patch-clamp experiments indicated that high supraclinical concentrations of propofol directly inhibited the cardiac K ATP -channel activity [18,19]. Ketamine also inhibits recombinant cardiac K ATPchannel activity in a concentration-dependent manner [20].…”
Section: Cardiac K Atp Channel (Sarcolemmal Channel)mentioning
confidence: 76%
“…Our previous studies demonstrated that propofol directly inhibited native and recombinant cardiac sarcolemmal K ATP channel activities during simulated ischemia [8,9]. These observations suggest that intravenous anesthetics may impair the endogenous organ protective mechanisms mediated by K ATP channels.…”
Section: Introductionmentioning
confidence: 91%
“…It also provides mitochondrial membrane stabilization via decreased mitochondrial calcium uptake and direct inhibition of mPTP [32]. In contrast to volatile anesthetics and opioids, its mechanism of action suggests that it does not trigger signaling pathways related to pre-or postconditioning, and thus lacks any conditioning effect in terms of myocardial protection against I-R injury [33]. Propofol's ability to preserve myocardial function after I-R injury may be attributable to the compensatory hypercontractile state of the non-ischemic region, whereas isoflurane is able to preserve the contractile function in the ischemic region [34].…”
Section: Propofolmentioning
confidence: 99%